(m-n+k)(m+7n-6k)=0

Simple and best practice solution for (m-n+k)(m+7n-6k)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (m-n+k)(m+7n-6k)=0 equation:


Simplifying
(m + -1n + k)(m + 7n + -6k) = 0

Reorder the terms:
(k + m + -1n)(m + 7n + -6k) = 0

Reorder the terms:
(k + m + -1n)(-6k + m + 7n) = 0

Multiply (k + m + -1n) * (-6k + m + 7n)
(k(-6k + m + 7n) + m(-6k + m + 7n) + -1n * (-6k + m + 7n)) = 0
((-6k * k + m * k + 7n * k) + m(-6k + m + 7n) + -1n * (-6k + m + 7n)) = 0

Reorder the terms:
((km + 7kn + -6k2) + m(-6k + m + 7n) + -1n * (-6k + m + 7n)) = 0
((km + 7kn + -6k2) + m(-6k + m + 7n) + -1n * (-6k + m + 7n)) = 0
(km + 7kn + -6k2 + (-6k * m + m * m + 7n * m) + -1n * (-6k + m + 7n)) = 0

Reorder the terms:
(km + 7kn + -6k2 + (-6km + 7mn + m2) + -1n * (-6k + m + 7n)) = 0
(km + 7kn + -6k2 + (-6km + 7mn + m2) + -1n * (-6k + m + 7n)) = 0
(km + 7kn + -6k2 + -6km + 7mn + m2 + (-6k * -1n + m * -1n + 7n * -1n)) = 0
(km + 7kn + -6k2 + -6km + 7mn + m2 + (6kn + -1mn + -7n2)) = 0

Reorder the terms:
(km + -6km + 7kn + 6kn + -6k2 + 7mn + -1mn + m2 + -7n2) = 0

Combine like terms: km + -6km = -5km
(-5km + 7kn + 6kn + -6k2 + 7mn + -1mn + m2 + -7n2) = 0

Combine like terms: 7kn + 6kn = 13kn
(-5km + 13kn + -6k2 + 7mn + -1mn + m2 + -7n2) = 0

Combine like terms: 7mn + -1mn = 6mn
(-5km + 13kn + -6k2 + 6mn + m2 + -7n2) = 0

Solving
-5km + 13kn + -6k2 + 6mn + m2 + -7n2 = 0

Solving for variable 'k'.

The solution to this equation could not be determined.

See similar equations:

| 4(-2+8n)=-136 | | X+2x+7x+9x+1=42 | | 14=21b | | 4(3-2x)=3(2-3x) | | -8=-2n | | -50=5d | | 135=-9k | | 3/4*x=2/7 | | 25x+71=156 | | 4(7x+8)+x=206 | | 2t=lb | | 6r=60 | | 3x+1+58x+33x=115 | | 75s=195 | | 2(-3)+2(-1)-(-3)(-1)+21= | | 3x+1+58x+13x=115 | | x(9+8)=33 | | =11.6 | | Y/3-3=-11 | | 12x+3=3(2x+6) | | 405.36=230+0.64x | | u+6u=14 | | -9+3v=v+3 | | x-3=-3-10x+7x | | -13+5x=x-1 | | 10n+15=9n+6n | | (3x^3/z)^3 | | 6x+21=7(x+3) | | 1-4k=-5k-1 | | -6-a=1+6a | | 5x-3=10x | | -5k+10k+16=1+2k |

Equations solver categories